DECISION SUPPORT SYSTEM FOR SCHOLARSHIP RECIPIENT SELECTION USING THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Mardhiah, Putri; Pratiwi, Mutiana; Akhiyar, Dinul; Arsyah, Ulya Ilhami (Jurnal Sains Informatika Terapan, 2024)
The advancement of science facilitates the development of new technologies that signify the progress of society. MTsS Muhammadiyah Kurai Taji aims to incorporate information technology into its data processing activities. Currently, the school relies on manual methods for processing student data, which often results in inaccuracies, particularly in classifying underprivileged students and other categories. This manual approach has led to challenges in maintaining valid data, which in turn complicates the decision-making process for scholarship allocations. To address these issues, the author proposes the development of a web-based A decision Support System (DSS). A DSS is a computer-based information system designed to support organizational decision-making. The proposed system will utilize MySQL database management to ensure the accuracy and validity of the data. By implementing this web-based information system, the school will benefit from increased time efficiency in data retrieval and scholarship processing. Additionally, this system will streamline reporting processes and improve the identification of students eligible for scholarship assistance, thereby addressing the current challenges faced by the school.